Nest survival of the Snowy Plover Charadrius nivosus at Marismas Nacionales, Nayarit - Lidiana Esther Ortega-Solis; Daniel Galindo-Espinosa; Elsa Margarita Figueroa-Esquivel; Uki Rosales-Huerta; John Cavitt; Fernando Puebla-Olivares (Huitzil, 2022)
Breeding habitat loss and nest predation are considered the main causes of Snowy Plover (Charadrius nivosus) populations decline worldwide. We evaluated the effects of season, nest age, distance to nearest vegetation patch, distance to nearest body of water, habitat type, and nesting substrate on the daily survival rate of Snowy Plover nests. During 2014-2015, we located 84 nests in Las Garzas-Chahuin-Chihua lagoon in Marismas Nacionales, Nayarit, Mexico. We used MARK software to estimate daily nest survival rate, which was 0.969 (95% CI = 0.95 - 0.97) for both breeding seasons combined, with a 42% finite nesting success. A total of 44 nests (52%) were successful, while 40 (48%) failed. The main causes of nest failure were predation (n = 30; 75% of failed nests) and flooding (n = 9; 22.5% of failed nests); one nest was lost due to unknown causes (2.5%). Daily survival rate increased with nest age and distance from the nearest vegetation patch. By contrast, daily survival rate decreased with the progression of the breeding season; a higher probability of nest success was evident when established early in the breeding season. Our results show the importance of different positive and negative factors influencing nest survival that might be considered as part of conservation strategies.